2012
DOI: 10.1242/dev.083873
|View full text |Cite
|
Sign up to set email alerts
|

BMP-dependent serosa and amnion specification in the scuttle fly Megaselia abdita

Abstract: SUMMARYBone morphogenetic protein (BMP) signaling is an essential factor in dorsoventral patterning of animal embryos but how BMP signaling evolved with fundamental changes in dorsoventral tissue differentiation is unclear. Flies experienced an evolutionary reduction of extra-embryonic tissue types from two (amniotic and serosal tissue) to one (amnionserosal tissue). BMP-dependent amnioserosa specification has been studied in Drosophila melanogaster. However, the mechanisms of serosal and amniotic tissue speci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
55
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(59 citation statements)
references
References 52 publications
4
55
0
Order By: Relevance
“…In flies, extraembryonic expression of Doc requires the combined activity of Dpp and Zen (Rafiqi et al, 2012;Reim et al, 2003). We therefore tested the expression of Tc-Doc in response to knockdown of Tc-dpp or Tc-zen1, the Tribolium orthologue of Dm-zen that is responsible for serosal specification (van der Zee et al, 2005).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In flies, extraembryonic expression of Doc requires the combined activity of Dpp and Zen (Rafiqi et al, 2012;Reim et al, 2003). We therefore tested the expression of Tc-Doc in response to knockdown of Tc-dpp or Tc-zen1, the Tribolium orthologue of Dm-zen that is responsible for serosal specification (van der Zee et al, 2005).…”
Section: Resultsmentioning
confidence: 99%
“…In dipterans that possess two EE membranes, Doc is initially expressed in a dorsal domain that comprises the prospective amnion and serosa, but is later excluded from the serosa (Anopheles: Goltsev et al, 2007;Megaselia: Rafiqi et al, 2010). It has been suggested that the repression of Doc from the serosa is mediated by persistent zen expression and a switch in its role from initial activation (Rafiqi et al, 2010(Rafiqi et al, , 2012Reim et al, 2003). Although Tc-Doc clears from the serosa during the SW stage (Fig.…”
Section: Evolution Of Dorsocross Expression and Functionmentioning
confidence: 97%
“…For example, in more primitive insects (e.g., beetles), the source of BMPs is not localized along the DV axis, but ventrally produced Sog helps BMPs diffuse to the dorsal side of the embryo (99) as it also does in Drosophila (21,24,29,57,(100)(101)(102)(103)(104)(105)(106). Also, in more primitive dipterans such as the scuttle fly, the BMP gradient is broken into two peaks that define distinct tissues in this species, the amnion versus the serosa, in contrast to Drosophila with single blended extra-embryonic tissue, the amnioserosa (107). In spiders, a cluster of Dpp-producing mesenchymal migratory cells leaves a trail of signaling that specifies the future dorsal midline that may be contacted by epithelial cells via cytonemes (108).…”
Section: Evolvability Of Bmp-mediated Patterningmentioning
confidence: 99%
“…In Drosophila, gbb and scw are expressed in distinct patterns, but both function as co-factors of the BMP network. A recent study indicates both Gbb and Scw are utilized for DV patterning in the scuttle fly (Rafiqi et al, 2012). gbb expression was also described in the early embryo of the lower Dipteran Clogmia albipunctata, in which the scw gene was not found (Wotton et al, 2013).…”
Section: Evolutionary Aspectsmentioning
confidence: 99%
“…A recent study suggests that the scw gene originated between the separation of the lineage leading to Brachycera and the origin of Cyclorrhapha through the duplication of another BMP5-8 gene, glass bottom boat (gbb), which is commonly found throughout the Arthropoda lineage (Wotton et al, 2013). Functional analysis in the scuttle fly Megaselia abdita suggests that both Gbb and Scw are utilized as co-factors of the BMP network for DV patterning (Rafiqi et al, 2012). In Drosophila, gbb expression is not observed in the early embryo, but Gbb plays a crucial role in posterior crossvein (PCV) formation during the pupal stage, at which an analogous mechanism utilizing a Gbb:Dpp heterodimer is needed for BMP signaling (Shimmi et al, 2005a;Matsuda and Shimmi, 2012;Shimmi and Newfeld, 2013).…”
Section: Introductionmentioning
confidence: 99%